Introducing, benefits & challenges of SAP BUSINESS ONE solution for small & mid-sized business ventures in Bangladesh by Kabeer Consulting Inc. - Chowdhury, Md. Abu Nayeem (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.